SDF-1/CXCR4 expression is an independent negative prognostic biomarker in patients with head and neck cancer after primary radiochemotherapy. Issue 1 (January 2018) - De-Colle, Chiara; Menegakis, Apostolos; Mönnich, David; Welz, Stefan; Boeke, Simon; Sipos, Bence; Fend, Falko; Mauz, Paul-Stefan; Tinhofer, Inge; Budach, Volker; Abu Jawad, Jehad; Stuschke, Martin; et al.
Abstract: Introduction: Preclinical and clinical data suggest that the chemokine pathway governed by SDF-1 and CXCR4 contributes to a resistant phenotype. This retrospective biomarker study aims to explore the specific prognostic value of SDF-1 and CXCR4 expression in locally advanced head and neck squamous cell carcinomas (HNSCC) treated with primary radiochemotherapy (RT-CT). Material and methods: Biopsies from 141 HNSCC tumours of the oral cavity, oropharynx and hypopharynx were evaluated for SDF-1 and CXCR4 expression by immunofluorescence. SDF-1 and CXCR4 expression was correlated with clinico-pathological characteristics and outcome after RT-CT. Results: Patients with tumours exhibiting overexpression of intracellular SDF-1 and CXCR4 have a higher risk for loco-regional relapse and a worse overall survival after RT-CT (multivariate analysis, hazard ratio 2.33, CI [1.18–4.62], p = 0.02 and hazard ratio 2.02, CI [1.13–3.59], p = 0.02, respectively). Similar results were observed when only the subgroup of HPV DNA negative patients were analysed (hazard ratio 2.23 and 2.16, p = 0.02 and p = 0.01, respectively). Conclusions: Our data support the importance of SDF-1 and CXCR4 expression for loco-regional control and overall survival in HNSCC after primary radiochemotherapy. Prospective multivariate validation and further studies into CXCR4 inhibition to overcome radiation resistance are warranted.